2012
DOI: 10.1007/s12020-012-9841-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity, restless legs syndrome, and health-related quality of life in type 2 diabetes

Abstract: To evaluate the relationship between physical activity with co morbidities and health-related quality of life in type 2 diabetic patients with and without restless legs syndrome (RLS). This is an observational study, set at tertiary care diabetic outpatient clinic, where 200 consecutive type 2 diabetic patients and 47 controls participated. Physical activity level was established by the International Physical Activity Questionnaire (IPAQ) and RLS diagnosis and RLS severity were established using the criteria d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…[4-5] A number of studies have shown racial disparities exist in diabetes self-management and psychosocial factors are an important consideration in care. [4-8]. …”
Section: Introductionmentioning
confidence: 99%
“…[4-5] A number of studies have shown racial disparities exist in diabetes self-management and psychosocial factors are an important consideration in care. [4-8]. …”
Section: Introductionmentioning
confidence: 99%
“…A possible mechanism is that decreased leptin levels and elevated ghrelin levels increase appetite and caloric intake and reduce energy expenditure, which facilitates the development of impaired glucose tolerance and obesity 14–16. In addition, patients with diabetes have more hypertension (76%), peripheral neuropathy (65%), and depressive symptoms (31%) 17. RLS is thus a significant sleep disorder that could be an important factor in diabetes management and health outcomes 18…”
Section: Introductionmentioning
confidence: 99%
“…As to treatment of RLS, physical activity is associated with a better perception of functional capacity, physical limitation, and pain in patients with diabetes with RLS 17. A large study involving 268 patients with diabetes showed that twice-a-week, supervised , aerobic and resistance training plus exercise and counselling for 12 months improves physical and mental Health-Related Quality of Life measures 19.…”
Section: Introductionmentioning
confidence: 99%
“…Three previously trained interviewers collected behavior questionnaires, demographic and clinical information using a face-to-face interview. Comorbidity severity was evaluated by the Charlson Comorbidity Index (CCI) [25] previously used in diabetic patients [26], depressive symptoms by the Beck Depression Inventory (BDI II) [27] previously validated [28] and sleep quality by the Pittsburgh Sleep Quality Index (PSQI) [29]. Levels of physical activity were evaluated by the International Physical Activity Questionnaire (IPAQ) [30,31].…”
Section: Assessmentmentioning
confidence: 99%